2015
DOI: 10.1016/j.astropartphys.2014.05.008
|View full text |Cite|
|
Sign up to set email alerts
|

Asymmetry of the angular distribution of Cherenkov photons of extensive air showers induced by the geomagnetic field

Abstract: The angular distribution of Cherenkov light in an air shower is closely linked to that of the shower electrons and positrons. As charged particles in extensive air showers are deflected by the magnetic field of the Earth, a deformation of the angular distribution of the Cherenkov light, that would be approximately symmetric about the shower axis if no magnetic field were present, is expected. In this work we study the variation of the Cherenkov light distribution as a function of the azimuth angle in the plane… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…6. The azimuthal symmetry is indeed almost restored after the application of the described procedure (however, this may not be the case for low-energy (E <1 PeV) or highly inclined (θ >1 rad) showers, see [51]). A part of the spatial histogram that became empty due to the shrinkage of the LDF was filled by the minimal value inside the shrinked part of the histogram.…”
Section: Eas Cherenkov Light Signal At the Ground Levelmentioning
confidence: 97%
“…6. The azimuthal symmetry is indeed almost restored after the application of the described procedure (however, this may not be the case for low-energy (E <1 PeV) or highly inclined (θ >1 rad) showers, see [51]). A part of the spatial histogram that became empty due to the shrinkage of the LDF was filled by the minimal value inside the shrinked part of the histogram.…”
Section: Eas Cherenkov Light Signal At the Ground Levelmentioning
confidence: 97%
“…To evaluate the angular resolution and effective area of HADAR in the 10 GeV to 100 TeV, we used the Cosmic Ray Simulations for Kascade (CORSIKA) program to generate a large number of extensive air shower samples, using the QGSJETII-04 and FLUKA models, respectively (Homola et al 2015), as shown in Figure 1.…”
Section: Experimental Sensitivitymentioning
confidence: 99%
“…The initiation of electromagnetic cascade showers was simulated using CORSIKA (Version 74100). The simulations considered primary incident γ-rays with different energies and at various zenith angles, traveling through an atmospheric medium at altitudes of 4300, 5300, and 6300 m. Specifically, high-and low-energy strong interaction models were established using QGSJETII-04 and FLUKA, respectively (Homola & Engel, 2015). To simulate Cherenkov radiation and the electromagnetic components in an EAS, an electromagnetic interaction model was established.…”
Section: Simulation Of Atmospheric Cherenkov Photonsmentioning
confidence: 99%